Household studies in complex societies: (micro)archaeological and textual approaches - Müller, Miriam (Oriental Institute seminars, 2015)
Introduction : household studies in complex societies : (micro)archaeological and textual approaches / Miriam Müller -- Investigating traces of everyday life in ancient households : some methodological considerations / Lynn Rainville -- Activity-area analysis : a comprehensive theoretical model / Peter Pfälzner -- How to reconstruct daily life in a Near Eastern settlement : possibilities and constraints of a combined archaeological, historical, and scientific approach / Adelheid Otto -- Ancient Egyptian houses and households : architecture, artifacts, conceptualization, and interpretation / Kate Spence -- Artifact assemblages in classical Greek domestic contexts : toward a new approach / Lisa C. Nevett -- Interaction between texts and social space in Mesopotamian houses : a movement and sensory approach / Paolo Brusasco -- Clean and unclean space : domestic waste management at Elephantine / Felix Arnold -- Creating a neighborhood within a changing town : household and other agencies at Amara West in Nubia / Neal Spencer -- Crucial contexts : a closer reading of the household of the Casa del Menandro at Pompeii / Jens-Arne Dickmann -- Private house or temple? : decoding patterns of the old Babylonian architecture / Peter A. Miglus -- Hybrid households : institutional affiliations and household identity in the town of Wah-sut (South Abydos) / Nicholas Picardo -- Living in households, constructing identities : ethnicity, boundaries, and empire in Iron II Tell en-Nasbeh / Aaron J. Brody -- Micro-archaeological perspectives on the Philistine household throughout the Iron Age and their implications / Aren M. Maeir -- Property title, domestic architecture, and household lifecycles in Egypt / Brian P. Muhs -- Late Middle Kingdom society in a neighborhood of Tell el-Dabʻa/Avaris / Miriam Müller -- Family structure, household cycle, and the social use of domestic space in urban Babylonia / Heather D. Baker -- Reconstructing houses and archives in early Islamic Jēme / Tasha Vorderstrasse -- Social conditions in the ancient Near East : houses and households in perspective / Elizabeth C. Stone -- Multifunctionality and hybrid households : the case of ancient Egypt / Nadine Moeller -- A Mesoamerican perspective on Old World household studies in complex societies / Cynthia Robin
Literaturangaben
Keywords: Konferenzschrift; Geschichte; Haushalt; Archäologie; Alter Orient